Dose field formation in thin films irradiated by electron beams: comparison of the Monte Carlo simulation with dosimetry - Kaluska, I.; Lazurik, V.T.; Lazurik, V.M.; Popov, G.F.; Rogov, Y.V.; Zimek, Z. (Харкiвський нацiональний унiверситет iм. В.Н. Каразiна, 2009)
The simulation of the absorbed dose distribution into thin films with different thickness inserted between flat boundaries of two homogeneous materials as well as the absorbed dose distribution near to boundaries of these materials irradiated with a scanned electron beam were fulfilled. Films inserted in multi-layer targets were parallel orientated with an incident electron beam (EB). The simulation was performed by the Monte Carlo (MC) method with utilization of the software ModePEB which was designed for predictions of a dose distribution in heterogeneous targets irradiated by EB with the electron energy range from 0.1 to 25 MeV. Comparison results of MC simulation with dosimetry for electron dose distribution formation in multi-layer targets with thin films is discussed. Проведено моделирование распределения поглощенной дозы в тонких пленках разной толщины, расположенных между плоскими границами двух гомогенных материалов, а также распределения поглощенной дозы вблизи границы этих материалов, облучаемых сканирующим пучком электронов. Пленки в многослойных мишенях были ориентированы параллельно падающему пучку электронов. Моделирование проводилось методом Монте Карло с использованием программы ModePEB, разработанной для предсказаний распределения дозы в гетерогенных мишенях, облучаемых пучком электронов с энергией от 0.1 до 25 МэВ. Обсуждается сравнение результатов Монте Карло моделирования с дозиметрией для формирования распределения дозы электронов в многослойных мишенях с тонкими пленками. Проведено моделювання розподілу поглиненої дози в тонких плівках різної товщини, розташованих між плоскими границями двох гомогенних матеріалів, а також розподіл поглиненої дози біля границі цих матеріалів, що опромінюються сканованим пучком електронів. Плівки у багатошарових мішенях були орієнтовані паралельно падаючому пучку електронів. Моделювання проводилось методом Монте Карло із використанням програми ModePEB, яку розроблено для передбачення розподілу дози в гетерогенних мішенях, що опромінюються пучком електронів з енергією від 0.1 до 25 МеВ. Обговорюються порівняння результатів Монте Карло моделювання із дозиметрією для формування розподілу дози електронів у багатошарових мішенях із тонкими плівками.
Keywords: розподіл дози; тонкі плівки; пучок електронів; програма ModePEB; dose distribution; thin films; electron beam; software ModePEB